ANALISIS PENGARUH DANA DEKONSENTRASI TERHADAP TINGKAT PRODUKSI PERIKANAN TANGKAP - Wirata . (Media Ekonomi, 2013)
Deconcentration and co-funds are used in order to create transparency and accountability, as well as proportionate in the allocation of these funds and fund assistance tasks, increase efficiency, effectiveness in managing these funds and fund assistance duties, giving advice to the ministries/agencies in planning the location and allocation of funds deconcentration and co-administration of funds for the right target and not concentrated in specific areas. Various studies and theories arise, but no one has examined the use of these funds has been distributed to the affected areas.This study examines how much these funds in influe the level of fish production in each province that has received funding deconcentration for the empowerment of coastal communities and efforts to increase the income of fishermen and the public welfare and marine fisheries.Keywords: deconcentration funds, the level of fishery production and efficiency                    and effectiveness